Pengaruh Kualitas Produk Makanan Terhadap Kepuasan Konsumen pada Restoran Hotel Salak The Heritage Bogor - Riani P. Ishak; Nisa Rahmaniyah Utami; Taufiq Kurniawan (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2022)
This study aims to determine and analyze the effect of product quality on customer satisfaction at the Hotel Salak The Heritage Bogor restaurant. Dimensions of product quality measured include presentation, menu variety, healthiness, delicacy, freshness and temperature. Dimensions of customer satisfaction measured are tangibles, reliability, responsiveness, empathy. This study uses a quantitative approach method. Collecting data using primary data through non-probability sampling/insendental sampling as many as 100 respondents who are guests who visit the restaurant. Data analysis in this study used simple linear regression with SPSS application, all research data were verified through all statistical tests. The results showed that the quality of food products has a positive and significant effect on customer satisfaction at the Salak Hotel Restaurant The Heritage Bogor.